Irradiation‑induced cellular senescence is linked to pro‑survival signaling and checkpoint regulation in a 2D and 3D model for head and neck cancer - Bugia, Luis; Affolter, Annette; Kern, Johann; Sohn, Emma; Jungbauer, Frederic; Fleckenstein, Jens; Lammert, Anne; Rotter, Nicole; Scherl, Claudia (Oncology reports, 2025)
Oncology Reports is an international journal devoted to fundamental and applied research in Oncology.